2018 International Workshop on Blockchain Oriented Software Engineering (IWBOSE) 2018
DOI: 10.1109/iwbose.2018.8327566
|View full text |Cite
|
Sign up to set email alerts
|

SmartInspect: solidity smart contract inspector

Abstract: Solidity is a language used for smart contracts on the Ethereum blockchain. Smart contracts are embedded procedures stored with the data they act upon. Debugging smart contracts is a really difficult task since once deployed, the code cannot be reexecuted and inspecting a simple attribute is not easily possible because data is encoded. In this paper, we address the lack of inspectability of a deployed contract by analyzing contract state using decompilation techniques driven by the contract structure definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…Liu et al [40] proposed to perform the fuzz testing on smart contracts by iteratively generating random but diverse transactions to detect reentrancy bugs. 1) Readability • Human readable code [34], [35] • Human readable execution [36], [37] • Re-entrancy [38], [39], [40] 2) Functional issues • Block randness [41], [42], [43] • Overcharging [44], [45] Deployment • Bytecode analysis [46], [47], [48], [49], [50], [51], [52], [53] 1) Contract correctness • Source code analysis [54], [55], [56], [57] • Machine learning based analysis [58], [59], [60] • Graph based analysis [61], [62] 2) Dynamic control flow • Path-searching [63] • Execution environment [64] Execution 1) Trustworthy oracle • Third-party involved [65] • Decentralized [66], [67] 2) Transaction-ordering dependence • Sequential execution [68] • Predefining contract [69] 3) Execution efficiency • Execution serialization [70], [71], [72] • Inspection of contract [73] Completion 1) Privacy and Security • Privacy [74],…”
Section: Recent Advances For Functional Issuesmentioning
confidence: 99%
“…Liu et al [40] proposed to perform the fuzz testing on smart contracts by iteratively generating random but diverse transactions to detect reentrancy bugs. 1) Readability • Human readable code [34], [35] • Human readable execution [36], [37] • Re-entrancy [38], [39], [40] 2) Functional issues • Block randness [41], [42], [43] • Overcharging [44], [45] Deployment • Bytecode analysis [46], [47], [48], [49], [50], [51], [52], [53] 1) Contract correctness • Source code analysis [54], [55], [56], [57] • Machine learning based analysis [58], [59], [60] • Graph based analysis [61], [62] 2) Dynamic control flow • Path-searching [63] • Execution environment [64] Execution 1) Trustworthy oracle • Third-party involved [65] • Decentralized [66], [67] 2) Transaction-ordering dependence • Sequential execution [68] • Predefining contract [69] 3) Execution efficiency • Execution serialization [70], [71], [72] • Inspection of contract [73] Completion 1) Privacy and Security • Privacy [74],…”
Section: Recent Advances For Functional Issuesmentioning
confidence: 99%
“…Torres, Schütte, and State [20] developed OSIRIS, a tool designed to scan integer vulnerabilities in Ethereum smart contracts. Bragagnolo et al [21] presented a SmartInspect architecture to inspect smart contracts. It addresses the lack of inspectability of a deployed contract by analyzing the contract state using decompilation techniques.…”
Section: Related Workmentioning
confidence: 99%
“…The Parity wallet case study clearly showed that a Blockchain-Oriented Software Engineering (BOSE) [13], [14], [15], [16], [17] is needed to define new directions to allow effective software development. New professional roles, enhanced security and reliability, modeling and verification frameworks, and specialized metrics are needed in order to drive blockchain applications to the next reliable level.…”
Section: Road Map To Bosementioning
confidence: 99%